DARI ANALISIS FOURIER KE ANALISIS WAVELET (From Fourier Analysis to Wavelet Analysis) - Martadiputra, Bambang Avip Priatna (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2001)
In this article we will compare the classical methods of Fourier analysis with the never methods of wavelet analysis. Fourier methods are not always a good tool to recapture the signal, particularly if it is highly non-smooth because too much Fourier information is needed to reconstruct the signal locally. In this case, wavelet analysis is often very effective because it provides a simple approach for dealing with local aspects of a signal.Key words: Fourier analysis, Wavelet analysis